Nuclear security culture assessment of medical facilities in Malaysia - Abdul Karim, Muhammad Khalis; Omar Baki, Sharudin; Jamaludin, Amirul Fakhruddin; Kayun, Zunaide; Ibahim, Mohammad Johari (Central Asian Studies, 2024)
National regulations are always consistent in providing the first layer of safety and security in nuclear-related medical facilities. Since its introduction, nuclear security has become the main focus of organizations to prevent any malicious activities due to internal and external threats made possible as harsh idealism growth is consistent with an increased number of populations. Briefly, the self-assessment allows an organization to develop and maintain a security culture among nuclear personnel by testing out knowledge and awareness involves radioactive sources. The objective of this study is to evaluate certain areas of an organization on nuclear security culture based on IAEA’s nuclear security model. A survey was performed on 117 radiological personnel that uses ionizing radiation sourcing from radioactive materials as well as irradiating apparatuses direct and indirectly by handing out cross-sectional questionnaires. The questions (scaled using numerical values, 1-7) were collected and categorized into several populations which are level of education, age, years of working and etc. The scores were then analyzed using appropriate statistical method. A report on strengths and weaknesses in several areas was given back to the organization for further development and enhancement of security. The study shows that awareness is greater within personnel with higher level of education. The results also showed an in awareness with age due to the fact that workers who are older portrayed a deeper understanding of what they are doing. There is a significant difference of scores in terms of duration of service where workers with 6-10 years of experience were more aware of the importance of security culture compared to those with 21-30 years of experience. In conclusion, it is found that there are several factors including the subject’s demographic that affect the level of awareness and knowledge among radiation personnel that works with radioactive materials.